Engineering And Innovation - An Evolutionary and Creative Enhancer of The Production and Technological Process in the Coffee Sector - Libardo Carlos VARGAS TABORDA (Communications of International Proceedings, 2025)
In a competitive global context, innovation and its application through technological tools supported by decision-oriented information systems become a pillar for sustainable development and the strategic consolidation of organizations. A company's ability to adapt, differentiate itself, and respond to market needs is related to its capacity for innovation and its differentiated application. This research proposes a methodology that applies its effectiveness based on the development and application of an Information System. This system combines approaches to creativity, innovation, and product development, applied and targeted to enhance the production processes of the coffee sector in Quindío, Colombia. The proposal, based on models such as Design Thinking, Lean Start-Up, and FORTH, includes the implementation of an Information System, which enables its practical application and decision-making regarding the development or evolution of coffee production. The objective is to promote bioeconomy and regional competitiveness and offer a replicable methodological alternative in other agroindustrial sectors. This development empowers coffee entrepreneurs to use technologies that empower them to appropriate and develop costing, design, differentiation, and decision-making, aligned with the principles of the bioeconomy and knowledge economy. This breaks paradigms, establishes new designs or differentiated product improvements, and strengthens production.
Keywords: Innovation; creativity; technology; and productivity.